Sociologia, semiotica e critica filosofico-letteraria. Ideologia dell’arte e arte dell’ideologia da Rossi-Landi e Bourdieu ad oggi (ENTHYMEMA, 2012)
With this article we aim to integrate the theoretic-philosophical reflection and the semantic-sociological approach within literary theory. In this way we aim to demonstrate the unexplored convergences between Bourdieu’s criticism against Heidegger’s ontology and Rossi-Landi’s studies on philosophy and ideology in general. Moreover, we will provide concrete examples of the application and further extensions of the proposed methodology for the criticism of ideology in the discourses about art and literature.